The Tourism, Hospitality and Events Student′s Guide to Study and Employability - Everett, Sally (SAGE Publications, Ltd. (UK), 2020)
This essential companion will guide you on your journey throughout your studies in tourism, hospitality and events management, from starting your university or college programme, to developing the essential skills needed for successful study and employment, to ensuring you perform well in assessments, through to applying for and securing a graduate level job and entering the workplace. Highly practical and accessible, chapters include: Think points to encourage you to pause and reflect on what the topic means for you Reflection exercises to help you evaluate your own skills, attributes and strengths/weaknesses Industry insights to offer you a unique view into the industry you’ll be working in Employer insights to provide you with real-world case examples from employers Student insights to show you different perspectives experienced by your peers Written by experts in the field, this friendly guide will provide you with everything you need to succeed and support you along every step of the way through your studies and into industry!